Comparison of the effects of alcoholic extract of aerial parts of Anvillea garcinii and atorvastatin on the lipid profile and thyroid hormones in hypercholesterolemic rats - Fatemeh Rasekh; Zohre Atashi-Nodoshan; Ali Zarei; Amir Abbas Minaeifar; Saeed Changizi-Ashtiyani; Zahra Afrasyabi (Mashhad University of Medical Sciences, 2022)
Objective: Decreased thyroid hormones along with increased blood fats and overweight, lead to atherosclerosis and eventually cardiovascular disease. The aim of this study was to compare the effects of alcoholic extract of aerial parts of Anvilea garcinii and atorvastatin on the lipid profile and thyroid hormones in hypercholesterolemic rats.Materials and Methods: In this study, 40 male Wistar rats were divided into 5 groups (n=8): control, hypercholesterolemic vehicle and three experimental groups. The control group, received water and normal food daily, the hypercholesterolemic vehicle group received drug solvent (atorvastatin dissolved in distilled water) and three experimental groups received alcoholic extract of A. garcinii (100 and 300 mg/kg) and atorvastatin (10 mg/kg) as gavage. At the end of the 45- day period, blood samples were prepared from all groups and the amount of desired factors was measured and analyzed.Results: The amount of lipid profiles (cholesterol, HDL, LDL, VLDL,TG) and thyroid stimulating hormone in the vehicle group were increased compared to the control group, while the amount of these factors were decreased in the experimental groups compared to the vehicle group. Furthermore, the level of thyroid hormones in the hypercholesterolemic vehicle group was decreased compared to the control group, while the level of these hormones was increased in the experimental groups receiving the extract compared to the vehicle group.Conclusion: Alcoholic extract of A. garcinii aerial parts, may increase thyroid hormones, and sequentially reduce blood lipids; thus, it could be a good candidate for the treatment of hypercholesterolemia and hypothyroidism.